Ultimate Solution Of Saw Dan Topsis Web-Based Methods For Scholarship Recipients At The Foundation Aldiana Nusantara - Taryo, Taswanda; Makhsun, Makhsun; Rizaldi, Devan; Sunarsi, Denok; Hamsinah, Hamsinah (Pasundan Social Science Development, 2025)
The role of information systems is currently crucial in various fields, including education and Yayasan Aldiana Nusantara (YAN), which supports many students from low to middle economic backgrounds, faces challenges in selecting scholarship recipients for financially disadvantaged students. To assist in making accurate and swift decisions, a computer-based Decision Support System (DSS) is required. This study aims to design a web-based DSS using the Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. This system was designed to assist Yayasan Aldiana Nusantara - YAN in selecting scholarship recipients based on criteria, such as, grade level, scholarship recipient status, father's income, mother's income, report card grades, and the number of extracurricular activities. The SAW method is used for weighting criteria, while the TOPSIS method is used to rank alternatives based on their proximity to the ideal solution. The system design follows the waterfall model, comprising analysis, design, implementation, and testing phases. The DSS is developed using PHP programming language and MySQL Database Management System. The system provides four types of access rights: administrator, jury, student, and faculty leader, ensuring security and ease of use. The test results indicate that the system has a high level of accuracy, reliability, integrity, and usability. This system also helps expedite the scholarship selection process, reduce errors in recipient determination, and facilitate the selection team in decision-making. With this DSS, YAN is able to conduct the scholarship selection process more effectively and efficiently, ensuring that aid is accurately targeted at students in need.